2019
DOI: 10.1159/000497446
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Incident Mortality in Dialysis Patients: Focus on Sex and Racial Disparities

Abstract: Background: Racial minorities and women constitute substantial portions of the incident and prevalent end-stage renal disease (ESRD) population in the United States. Although ESRD is characterized by high mortality, temporal trends, and race and sex differences in mortality have not been studied. Methods: We evaluated 944,650 adult patients who initiated dialysis between January 1, 2005 and December 31, 2014, using the United States Renal Data System, for sex-related and race-related trends in mortality. Logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Although the mortality rate among hemodialysis (HD) patients is on a steady decline, it is still higher than that of the general population [1,2]. Various risk factors for worse survival rates have been reported [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mortality rate among hemodialysis (HD) patients is on a steady decline, it is still higher than that of the general population [1,2]. Various risk factors for worse survival rates have been reported [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Vart et al indicated in a meta-regression analysis study that race is possibly related to the degree of association between low SES and CKD (P value = 0.001) [19]. Additionally, they demonstrated that the relative risk (RR) of CKD in low-SES people was 58% higher in African Americans (RR, [24]. Noori et al demonstrated that there was a strong association between higher levels of C-reactive protein (CRP) and interleukin-6 (IL-6) and an increase in the adjusted mortality risks of 799 African American and white dialysis patients followed over six years [25].…”
Section: Race and Ckdmentioning
confidence: 99%
“…However, the preponderance of ESRD is higher for minorities than their non-Hispanic white counterparts ( Table 2). The study by Shah et al concluded that even though the likelihood of death is higher in African Americans with CKD than in non-Hispanic individuals with CKD, once ESRD is established, there is a reversal in the trend [24]. The racial/ethnic differences in inflammation highlighted by Noori et al may be the reason for the unexpected difference in survival between African American and white patients on dialysis [25].…”
Section: Race and Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…USRDS data for 944,650 dialysis patients for 2005 – 2014 found that the 1 year adjusted mortality rates were lower for blacks (OR 0.73), Hispanics (OR 0.64), Asians (OR 0.55) and Native Americans (OR 0.67) compared with whites (CR 1.0); over the study period mortality rates fell for both men (28.3% to 20.2%) and women (28.4% to 20.7%). Closer analysis found that the survival advantage for women (observed in 2005) changed to an advantage for men (observed in 2014), quite different from the gender difference favoring women in the general population …”
mentioning
confidence: 99%